2013
DOI: 10.1101/gr.151670.112
|View full text |Cite
|
Sign up to set email alerts
|

Genome evolution during progression to breast cancer

Abstract: Cancer evolution involves cycles of genomic damage, epigenetic deregulation, and increased cellular proliferation that eventually culminate in the carcinoma phenotype. Early neoplasias, which are often found concurrently with carcinomas and are histologically distinguishable from normal breast tissue, are less advanced in phenotype than carcinomas and are thought to represent precursor stages. To elucidate their role in cancer evolution we performed comparative wholegenome sequencing of early neoplasias, match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
117
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(126 citation statements)
references
References 45 publications
9
117
0
Order By: Relevance
“…[14][15][16][17] Accumulating evidence suggests that PIK3CA point mutations may also be common in other proliferative breast lesions such as benign papillomas and columnar cell lesions. [18][19][20][21][22][23] Prior studies have failed to identify PIK3CA mutations in histologically normal breast tissue, even with the same sensitive methods employed here. 1,8,16,19 In this study, we demonstrated a 50% frequency of PIK3CA point mutations in usual ductal hyperplasia and columnar cell lesions across 62 lesions, representing the largest series to date.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…[14][15][16][17] Accumulating evidence suggests that PIK3CA point mutations may also be common in other proliferative breast lesions such as benign papillomas and columnar cell lesions. [18][19][20][21][22][23] Prior studies have failed to identify PIK3CA mutations in histologically normal breast tissue, even with the same sensitive methods employed here. 1,8,16,19 In this study, we demonstrated a 50% frequency of PIK3CA point mutations in usual ductal hyperplasia and columnar cell lesions across 62 lesions, representing the largest series to date.…”
Section: Discussionmentioning
confidence: 93%
“…(43) Li et al 16 studied PIK3CA mutations in usual ductal hyperplasia and found no mutations in 16 lesions, in contrast to our results; the differences may be due to sample size and methodologic sensitivity, as they used less-sensitive direct Sanger sequencing. 16 The activating PIK3CA hotspot mutations seen frequently in breast cancers and proliferative lesions, most notably H1047R, E542K and, E545K, have transforming potential when overexpressed in a variety of cell culture models, [8][9][10] which arise before the most common ancestor in the genomic history of several breast carcinomas 23,44 and have thus been logically viewed as drivers of carcinogenesis. Interestingly, expression of the PIK3CA H1047R mutation at physiologic or inducible supraphysiologic levels in the mouse mammary gland leads to increased branching, duct dilation, and luminal epithelial hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S14). Evolutionary phylogenies were constructed using the somatic mutation hierarchy algorithm (20,47) in 22 patients for whom multiple tumors were interrogated by exome sequencing, using all detected somatic mutations. Enrichment of mutations within EIPs was tested using a Fisher exact test with a Bonferroni correction for multiple hypothesis testing.…”
Section: Methodsmentioning
confidence: 99%
“…With fractions of mutated alleles evolving over time, the study of the exact mutated allele fractions, of their subclonal distribution and possible role in clonal evolution gains more importance (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%